1932
DOI: 10.1017/s0021859600054113
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Balance Studies on Poultry

Abstract: SINGULARLY few records of mineral balance studies on poultry have appeared in the literature. The difficulty of separating faecal excrement from urinary excrement has probably been responsible for this. At the same time such studies may yield information, even if the separation of faeces and urine is not carried out.Hainan (i) conducted balance experiments on two pullets over a period of 14 weeks; he found that storage of calcium, phosphorus and nitrogen occurs during only a short period before laying; the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
23
2

Year Published

1933
1933
1984
1984

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 8 publications
4
23
2
Order By: Relevance
“…The level of calcium excretion during the laying period was of the order of 0-25 gm. CaO per diem, in agreement with previous observations (3).…”
supporting
confidence: 93%
See 3 more Smart Citations
“…The level of calcium excretion during the laying period was of the order of 0-25 gm. CaO per diem, in agreement with previous observations (3).…”
supporting
confidence: 93%
“…The figures for Hainan's other pullet lead to much the same result. The CaO/P 2 O 5 ratio of Hainan's ration (Ca0/P 2 0 5 = 1-33) did not diverge so very widely from that of tricalcium phosphate (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18); it is obvious that if CaO and P 2 O 5 were being retained in a ratio not greatly different, then the ratio in the droppings was bound to be almost the same. When viewed from the standpoint expressed here, Hainan's data cannot be regarded as necessarily establishing that calcium and phosphorus were being excreted together by his pullets as tricalcium phosphate.…”
Section: Discussion Of Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…These changes were first observed in the blood of pigeons by Riddle and Reinhart (1926), who observed a rise in the level of blood calcium from 9.3 milligrams/lOO milliliters in the non-reproductive female to a value greater than 20 milligrams/lOO milliliters at the time of ovulation. Common (1932) conducted balance experiments on pullets entering their production cycles. He observed that approximately ten days prior to the onset of production there was a large increase in the quantities of calcium and phosphorus retained from the diet.…”
Section: Review Of Literaturementioning
confidence: 99%